2022
DOI: 10.18231/j.pjms.2022.095
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity: Risk factors and associated co-morbidities

Abstract: To estimate the prevalence of ROP and identify risk factors and co-morbidities associated with it. This cross-sectional study was performed, enrolling all premature babies admitted to the NICU of Jawaharlal Nehru Medical College and Hospital, A.M.U., Aligarh, Uttar Pradesh over 18 months. Various risk factors and co-morbidities for ROP were assessed using univariate and multivariate analysis. Out of the studied 164 infants, 29 infants (17.68%) developed ROP in one or both eyes; 51.72% (15/29) had stage 1, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 18 publications
1
4
1
Order By: Relevance
“…There was no much difference in incidence of ROP among male and female babies in our study which is similar in other studies. [10][11][12] The mean gestational age was 32.44 ± 2 weeks in this study and mean birth weight was 1.59 ± 0.36kg which corelated with the study by Dwivedi A et al reported Mean gestational age (GA) of 33.28 ± 0.105 and mean birth weight (BW) was 1.63 ± 0.015. 7 And a study by Kumar et al which showed mean birth weight and gestation of the infants screened for ROP as1335±351 g and 31±2.2 wks, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…There was no much difference in incidence of ROP among male and female babies in our study which is similar in other studies. [10][11][12] The mean gestational age was 32.44 ± 2 weeks in this study and mean birth weight was 1.59 ± 0.36kg which corelated with the study by Dwivedi A et al reported Mean gestational age (GA) of 33.28 ± 0.105 and mean birth weight (BW) was 1.63 ± 0.015. 7 And a study by Kumar et al which showed mean birth weight and gestation of the infants screened for ROP as1335±351 g and 31±2.2 wks, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…12 The research conducted by Rizvi SA et al found that there was a strong relationship between the development of ROP and gestational age, LBW, multiple gestation, a history of blood transfusion, respiratory distress syndrome, and infection. 10 However, we found that there is no significant association between ROP and sex, neonatal jaundice.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations